2020
DOI: 10.3389/fmicb.2020.01746
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota in Dung and Milk Differ Between Organic and Conventional Dairy Farms

Abstract: Organic farming is increasingly promoted as a means to reduce the environmental impact of artificial fertilizers, pesticides, herbicides, and antibiotics in conventional dairy systems. These factors potentially affect the microbial communities of the production stages (soil, silage, dung, and milk) of the entire farm cycle. However, understanding whether the microbiota representative of different production stages reflects different agricultural practices-such as conventional versus organic farming-is unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Micropepsaceae (F) information is scarce but has been found in acidic soils and is involved with carbon cycling [58]. Tepidisphaerales (O) has little information available except for an association with conventional farming [59], and WD2101(F) is polysaccharide degraders found in raised bogs and eutrophic fens [60]. Similarly, Ktedonobacterales (O) is relatively unknown but have been found to inhabit forests, gardens, and sand in low numbers, as well as extreme environments, such as volcanoes and geothermal areas [61].…”
Section: Discussionmentioning
confidence: 99%
“…Micropepsaceae (F) information is scarce but has been found in acidic soils and is involved with carbon cycling [58]. Tepidisphaerales (O) has little information available except for an association with conventional farming [59], and WD2101(F) is polysaccharide degraders found in raised bogs and eutrophic fens [60]. Similarly, Ktedonobacterales (O) is relatively unknown but have been found to inhabit forests, gardens, and sand in low numbers, as well as extreme environments, such as volcanoes and geothermal areas [61].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that diet has a direct impact on the gut, rumen, and milk microbiota of bovines [87][88][89]. To our knowledge, only one study has compared the microbiota of dairy cows from conventional and organic farming [27]. This study demonstrated that the microbiome of the cow's gut and milk was significantly different between agricultural management systems, while no differences were found in the microbial communities of soil and silage [27].…”
Section: Microbiological Qualitymentioning
confidence: 73%
“…To our knowledge, only one study has compared the microbiota of dairy cows from conventional and organic farming [27]. This study demonstrated that the microbiome of the cow's gut and milk was significantly different between agricultural management systems, while no differences were found in the microbial communities of soil and silage [27]. Milk samples from organic farms were significantly associated with the family Rhodobacteraceae and elevated levels of Ruminococcaceae.…”
Section: Microbiological Qualitymentioning
confidence: 89%
See 1 more Smart Citation